2018
DOI: 10.1177/1120672118766809
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and higher order aberrations after bilateral implantation of an extended depth of focus intraocular lens

Abstract: The TECNIS Symfony intraocular lens can be considered an appropriate alternative to multifocal intraocular lenses because of good visual results at far, intermediate, and near distance as well as in low-contrast vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 31 publications
6
29
1
1
Order By: Relevance
“…Some clinical measurements of straylight and its effects in eyes implanted with the same IOL models tested here 18,19 are not in full agreement with our findings. However, it is necessary to take into account that straylight is commonly reported as a single value that corresponds with the average over a defined angular range.…”
Section: Discussioncontrasting
confidence: 66%
“…Some clinical measurements of straylight and its effects in eyes implanted with the same IOL models tested here 18,19 are not in full agreement with our findings. However, it is necessary to take into account that straylight is commonly reported as a single value that corresponds with the average over a defined angular range.…”
Section: Discussioncontrasting
confidence: 66%
“…Of 10 studies potentially relevant for this meta-analysis, one study enrolling patients with preexisting corneal astigmatism of 1.00 D or worse was excluded [17]. Ultimately, 9 studies were included in our quantitative analysis [9,10,[18][19][20][21][22][23][24]. Table 1 summarizes the characteristics and quality of the 9 studies that met all inclusion criteria [9,10,[18][19][20][21][22][23][24].…”
Section: Results Of the Searchmentioning
confidence: 99%
“…Six studies [9,10,19,21,22,24] reported spectacle independence. There was a significant difference in the overall effect that favored higher spectacle independence with EDOF IOLs than with monofocal IOLs (RR: 2.81, 95% CI: 1.06 to 7.46, P = 0.04) ( Figure 4A).…”
Section: Spectacle Independencementioning
confidence: 99%
“…Seven studies [10,18,[20][21][22][23][24] reported contrast sensitivity and the results are summarized in Table 3.…”
Section: Contrast Sensitivitymentioning
confidence: 99%
“…Table 3. Two studies reported no significant difference in halos between EDOF and monofocal IOLs [20,21]. The U.S. FDA clinical trial reported that EDOF IOLs resulted in more frequent halos than monofocal IOLs [24].…”
Section: Contrast Sensitivitymentioning
confidence: 99%